Perbedaan Skor Pengetahuan dan Sikap Wanita Usia Subur (WUS) Tentang Deteksi Dini Kanker Serviks Antara Pemanfaatan E-Booklet dengan Lembar Balik - Ni Made Ari Suciani; Ni Komang Yuni Rahyani; Ni Nyoman Suindri; Ni Luh Putu Sri Erawati; Listina Ade Widya Ningtyas (Universitas Pahlawan Tuanku Tambusai, 2025)
Women often struggle to detect cervical cancer early because of a lack of awareness and knowledge. Puskesmas Kuta Utara's data shows that the early detection coverage for cervical cancer is 102 people (1.46%) in 2023, still below the target (80%). This study aims to compare the knowledge and attitudes of women regarding early detection of cervical cancer using an e-booklet and flip sheet among women of childbearing age. Researchers utilized a Quasi-Experimental Design research approach involving a pretest-posttest control group design. Purposeful sampling involved two groups of WUS, with 30 individuals in the e-booklet group and 30 in the flipchart group. The sampling technique used was purposive sampling.The research was conducted in April 2024, and data was collected by distributing questionnaires on knowledge and attitudes. The data was analyzed using univariate and bivariate methods, including wicolxon and mann-whitney because the results of the data normality test show that the data is not normally distributed. The results revealed that the knowledge scores for the e-booklet group were compared to the flipchart group, yielding a of p 0.04 (p<0.05). Similarly, the attitude scores for the e-booklet group compared to the flipchart group resulted in a of p 0.02 (p<0.05). It can be concluded that there is a difference in the knowledge scores and attitudes of women of childbearing age (WUS) regarding early detection of cervical cancer when compared with the use of e-booklets and flip charts. Health workers are expected to use e-booklets for health promotion because they are more effective in increasing knowledge and changing women's attitudes towards early detection of cervical cancer.